2021
DOI: 10.33596/coll.76
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Shared: Implementation of a Randomized Clinical Trial for Alcohol Use Disorders with Five American Indian and Alaska Native Communities

Abstract: This paper examines how five Tribal communities and an academic institution developed the Helping Our Native Ongoing Recovery Project. The goal of this study was to conduct a large randomized controlled trial using contingency management as an intervention for alcohol use disorders among 400 American Indian and Alaska Native (AI/AN) people. Using a community-engaged approach, including tenants of community-based participatory research and the Quality Implementation Framework, close collaboration between Tribal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Out of the 20 studies reviewed, ten (50%) of them reported outcomes related to intervention effectiveness ( 1 , 34 , 36 , 38 , 40 , 41 , 45 , 48–50 ). There were several studies where the primary outcome was tobacco cessation [ n = 7; ( 32 , 36 , 38 , 45 , 47–49 )].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 20 studies reviewed, ten (50%) of them reported outcomes related to intervention effectiveness ( 1 , 34 , 36 , 38 , 40 , 41 , 45 , 48–50 ). There were several studies where the primary outcome was tobacco cessation [ n = 7; ( 32 , 36 , 38 , 45 , 47–49 )].…”
Section: Resultsmentioning
confidence: 99%
“…Including enhancements to Adoption focused on the staff members themselves. While some studies had specific inclusion and exclusion criteria for staff ( 32 , 38 , 48 ), Indigenous staff and level of staff buy-in were highlighted as the key to increasing Adoption ( 37 , 41 , 44 ). The duration of the intervention also impacted Adoption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has highlighted opportunities to partner with programs outside of the treatment context to sustain CM within Tribal communities. With the necessary infrastructure in place, other grant funding could also be sought to strengthen sustainability 38 . Furthermore, the research team continues to support and partner with Tribal communities by offering CM training and technical support to enhance implementation and sustainment of CM.…”
Section: Discussionmentioning
confidence: 99%
“…With the necessary infrastructure in place, other grant funding could also be sought to strengthen sustainability. 38 Furthermore, the research team continues to support and partner with Tribal communities by offering CM training and technical support to enhance implementation and sustainment of CM. In addition, policy efforts have recently been undertaken to reduce barriers to delivering CM (eg, restrictions around incentives).…”
Section: Discussionmentioning
confidence: 99%